Main puteri and wayang kulit : An analysis on magic belief among the Malay community In Malaysia. Study in Terengganu and Kelantan. - Wan Nor Jazmina, Wan Ariffin; Nor Izzati, Abd Ghani (2019)
The traditional Malays belief in animism and the existence of magical elements which dominated and controlled the whole of the nature [1]. Historically, Malays had experienced several phase of changes that influenced their belief beginning with animism, Buddhism, Hinduism and ended with Islam. In spite of Islam became the religion of Malays, there are also have other belief which contradict with Islam. Mohd Taib Osman [2] outlined five beliefs in the Malay community. It consist of believe in Allah and the Prophet, versus of the Quran, the elements of spirits, extraordinary powers and the element of magic. The view of the existence of magic among Malays affected their daily life in some aspects. This beliefs was manifested clearly in some of the traditional culture art performances include Main Puteri and Wayang Kulit (shadow play). Therefore, this paper will explain in details regarding to the several items in these cultural performances which could be the evidences about the belief in magic in Malay‟s world-view. Under this scope, researcher used three techniques of data collection; interview, participant observation and document analysis for completing the study. The study have shown that the Malay have their own perception about the element of magic in their daily life generally and particularly in these cultural art performances. The trust and the recognition about the elements of magic in Malay mindset such as spirits of the dead, ghost and deities have clearly exposed in Main Puteri and Wayang Kulit show. Therefore, this paper is expected to expose the current Malay‟s belief on the magic element through these two cultural art performances, Main Puteri (Princcess Play) and Wayang Kulit (Shadow Play).